Safeguards Assessments-2009 Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper provides Executive Directors with an update of safeguards assessment activities from July 1, 2008 through June 30, 2009. In common with previous updates, it covers the various types of safeguards activities undertaken during the year, highlighting the increased activity associated with the 'twin crises' of food and fuel price shocks and the global financial crisis during 2008/09. It also briefly discusses developments in the latter part of that year, including the separate safeguards procedures introduced for members accessing the Flexible Credit Line (FCL).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet